SPECIFIC ASPECTS OF THE USE OF MODELING TECHNIQUES IN SOLVING ISSUES RELATED TO PHYSICS (E Conference Zone, 2022)
This article analyzes the peculiarities of adaptation to the method of modeling in solving physical problems. In addition, the methods of modeling the stages of educational issues in physics and the generalized methods of solving the issues on the basis of the analysis of cognitive activity were discussed.